You don't need to forgive : trauma recovery on your own terms - Gregory, Amanda Ann (Minneapolis : Broadleaf Books, 2025)
"Feeling pressured to forgive offenders is a common reason why trauma survivors avoid mental health services and support. Trauma psychotherapist Amanda Ann Gregory explores the dangers of forced forgiveness and the benefits of elective forgiveness, which gives survivors the agency to progress in their recovery on their own terms"--
Introduction -- Trauma: What it Is, and What it Is Not -- Forgiveness: What it Is, and What it Is Not -- The Limitations of Forgiveness Research and Forgiveness Therapy -- Safety Precedes Forgiveness -- Destigmatizing and Embracing Anger -- Shame Obstructs Forgiveness -- Recognizing Religious Influences -- Forgiving and Social JusticeResponding to Forgiveness Advocates -- Embracing Elective Forgiveness -- Twenty Trauma Recovery Methods -- Conclusion.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Forgiveness -- Psychological aspects; Psychic trauma -- Treatment; Pardon -- Aspect psychologique; Traumatisme psychique -- Traitement